(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Home range, activity pattern and breeding aspects of the pariah dog (Canis lupus familiaris Linnaeus, 1786) were studied at the Chittagong University Campus in Chittagong of Bangladesh during September 2012 to January 2013. The average home range encircled during daytime by a pack was 10,120 m2. The activity pattern of two dog packs was monitored through scan sampling methods at 15 minutes intervals. The dogs spent their diurnal time in resting (24.5%), sitting and basking (17.1%), standing (2.4%), moving and walking (16.2%), running (17.5%), sleeping (5.3%), feeding, foraging and drinking (6.3%), social behavior (2.9%) and territorial behavior (7.8%). Parturition occurred from September to January and the peak period was in November. The average litter size was 4.7 (range 1-12, n=10). and the overall survival rate of puppies was 2.6 per litter (i.e., 55.32%) up to January. The Chittagong Univ. J. B. Sci. 8(1&2): 21-32, 2013